Pengaruh Cakupan Layanan Kesehatan dan Kelas BPJS terhadap Taksiran Berat Janin pada Ibu Hamil - hutagaol, rutmauli; Fauziah, Erna; Sesaria, Tiffany Gita; Anhar, Citra Amaniah; Ardiansyah, Fakrul (Jurnal Skala Kesehatan, 2025)
Estimated Fetal Weight is one of the important indicators in monitoring fetal growth during pregnancy. In addition to biological factors, the health services received by pregnant women and BPJS membership classes are suspected to have influenced TBJ. This study aimed to analyze the effect of health service coverage and BPJS classes on TBJ in pregnant women. This study uses a cross-sectional design with a retrospective approach. Data was taken from the medical records of 152 pregnant women participating in BPJS who were treated at two regional hospitals in South Kalimantan during 2024. The variables analyzed included the mother's age, education, gestational age, BPJS class, and the number of service types received. Data analysis was conducted using the chi-square test and logistic regression. The results of the analysis showed that gestational age, parity, and BPJS class had a meaningful relationship with TBJ. From the logistic regression analysis, the level of education (p = 0.034; OR = 0.580) and gestational age (p = 0.020; OR = 0.577) had a significant effect on TBJ. Although not statistically significant, the type of service showed the highest odds ratio value (OR = 2.108), indicating that the more types of services received, the greater the chances of TBJ being in the normal category. TBJ is influenced by educational factors, gestational age, and BPJS classes attended by pregnant women. Improving the quality and equitable distribution of health services, especially for low-class BPJS participants, is very important to support optimal fetal growth.